Dentable functions and radially uniform quasi-convexity - Carl G. Looney (International Journal of Mathematics and Mathematical Sciences)
In this paper we give a further result which states sufficient conditions for the theory of convergence of minimizing sequences to be applicable, develop the theory further, and give an application.